Pengaruh Edukasi Fintech dan Literasi Ekonomi Digital Terhadap prilaku Digital Remaja - Anisa, Anisa; Hafsari, Nia maulidani; Nisa', Indah Khaerun; Aini, Qurratul; Rizkiwati, Baiq Yuliana (Universitas Hamzanwadi, 2025)
The development of financial technology (fintech) is driving changes in adolescent consumption behavior toward digital. This study aims to analyze the influence of fintech education and digital economic literacy on adolescent digital consumption behavior. The research method used a quantitative approach with a survey of 100 adolescents aged 18–25 who are active fintech users. Data were analyzed using multiple linear regression. The results show that fintech education and digital economic literacy have a positive and significant influence on adolescent digital consumption behavior, both partially and simultaneously, with fintech education as the most dominant variable. These findings emphasize the importance of improving fintech education and digital economic literacy, accompanied by strengthening self-control for more judicious use of digital financial services.